SUFI ULAMA DA'WAH ACTIVITIES IN BARUS: A HISTORICAL OVERVIEW - Ali Mahmud Ansyari; Mailin Mailin; Hasnun Jauhari Ritonga (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
Da’wah is an obligation for followers of Islam, whose purpose is to spread the teachings of Islam and build an Islamic society. Da''wah, Tabligh, Taghyir, amar ma''ruf nahi munkar, and morals—even the Qur''an says that the best ummah is to do ''amar ma''ruf nahi munkar. Even the Qur''an lists the ethics of da''wah contained in Surah An-Nahal verse 125, which starts from bil-hikmah, mau''izho hasanah, and wajadilhu billati hiya ahsan. In delivering dawah, someone needs a pattern of da''wah in his delivery, including Ulama, and the Ulama referred to here are Ulama from among Sufis, where we know the first preachers who preached in Indonesia were mostly from among Sufi Ulama and had an influence on the entry of Islam into Indonesia by peaceful means. So researchers get some problems about how the pattern of da''wah in Barus which became the location of the first time this Sufi Ulama spread Islam in Indonesia, as we know, the pattern of da''wah of Sufi Ulama is the basic pillar of spreading Islam without violence, running peacefully. This research is focused on the historical study of the History of the Development of Da''wah in Sufi Ulema. Spreading Islam in Barus requires a historical approach.he method used in this study is a qualitative method with a descriptive approach and library research, namely problem-solving procedures that are investigated by describing the state of the subject or object in the study, which can be people, institutions, society, and others who are currently based on facts that appear or as they are, and collecting data on a number of works of other figures and writers related to the topic of discussion. Da''wah is a definite part of the lives of religious people. In the teachings of Islam, it is an obligation imposed by the religion on its adherents, both those who have embraced it and those who have not. Thus, da''wah does not merely arise from individuals or groups, although at least there must be a group that does it. In delivering da''wah, the Prophet, on the one hand, faced very severe challenges but, on the other hand, found a positive response from various circles, especially weak people.